Analisis Uji Kelayakan Rumah Sakit TK III DR. R. SOEHARSONO Terhadap Aspek Operasional dan Pelayanan Kesehatan - Puspitasari, Aulia; Kumalawati, Rosalina; Normelani, Ellyn (COMPACT: Spatial Development Journal, 2024)
This study aims to conduct a feasibility test on the DR. R. Soeharsono Class III Hospital, focusing on evaluating operational aspects, facilities, and human resources. This study uses a qualitative descriptive approach by collecting data through observation and document analysis. Evaluations were carried out on several main indicators, namely infrastructure, medical services, equipment availability, operational efficiency, and financial feasibility. The results of the feasibility test indicate that the DR. R. Soeharsono Class III Hospital has strengths in competent human resources and a strategic location. However, there are several obstacles such as the need to improve medical technology, improve operational management, and more effective financial management. Overall, the hospital is declared eligible to continue its operations with recommendations for development in the field of technology, ongoing training for medical staff, and strengthening marketing strategies to increase competitiveness. The results of this study are expected to be a reference for management in making strategic decisions to improve the quality of health services at Class III Hospital DR. R. Soeharsono.